Improving the accuracy of contact-type drawbead elements in panel stamping analysis - Firat, Mehmet; Livatyali, Haydar; Cicek, Orhan; Onhon, M. Fatih (Elsevier BV, 2009)
Abstract A finite element modeling technique is proposed to improve the accuracy of contact-type drawbead elements in panel forming analyses, and a performance assessment in terms of part border and thickness predictions is presented in conjunction with panel stamping experiments of two automotive sheets. Inherent model limitations causing incorrect part geometry and thickness predictions are, firstly, evaluated considering blank deformations on a plain–strain section of a stamping die. The influence of omitted drawbead geometry and overestimated drawbead exit thickness are described analytically, and a closed form expression is obtained to correct draw-in model error. Then a sectional deformation model is used to calculate restraint force and drawbead exit thickness for a particular blank and drawbead design. The proposed technique is applied in process modeling of polygon shaped panels made of draw-quality and bake-hardenable steels. Three bead penetrations were investigated in process simulations as well as in stamping experiments. The same blankholder force was applied in all process conditions. Computed draw-in and thickness distributions were compared with on-part measurements using an experimental panel-draw die. It was determined that drawbead models based on force parameters only resulted in remarkably high thickness values at the die entry and mostly overestimated draw-in along panel border lines. An evaluation of thickness distributions computed with proposed technique showed an improved correlation with experiment results of both blank materials and confirmed the use of the drawbead exit thickness as a drawbead modeling parameter. Effects of bead penetration on panel border lines were also simulated in accord with stamping experiments.
Keywords: Materials Science